Sales structure and its impact on accuracy of short-term sales forecasting in manufacturing companies - Paták, Michal; Vlčková, Vladimíra (University of Pardubice, 2013)
The article deals with the issue of the hierarchical sales forecasting in manufacturing companies and focuses on the specifics of those companies whose customers are mainly intermediaries operating on B2C markets. The article proposes a hierarchical forecasting models while determining their accuracy in short-term sales forecasting in a selected company of chemical industry. Through the forecasting model accuracy analysis, the impact of aggregation level of sales on the forecasting accuracy was studied.